Fekete-Szegö problems for generalized Sakaguchi type functions associated with quasi-subordination - PANIGRAHI, Trailokya; RAINA, Ravinder Krishna (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In the present paper, the authors introduce a generalized Sakaguchi type non-Bazilevic function class Mλ,β (φ, s, t) of analytic functions involving quasi-subordination and obtain bounds for the Fekete-Szegö functional |a3 −µa2 for the functions belonging to the above and associated classes. Some important and useful special cases of the main results are also pointed out. Mathematics Subject Classification (2010): 30C45, 33C50, 30D60.